Control of periplasmic interdomain thiol:disulfide exchange in the transmembrane oxidoreductase DsbD. - Mavridou, D; Stevens, J; Goddard, A; Willis, A; Ferguson, S; Redfield, C (2009)
The bacterial protein DsbD transfers reductant from the cytoplasm to the otherwise oxidizing environment of the periplasm. This reducing power is required for several essential pathways, including disulfide bond formation and cytochrome c maturation. DsbD includes a transmembrane domain (tmDsbD) flanked by two globular periplasmic domains (nDsbD/cDsbD); each contains a cysteine pair involved in electron transfer via a disulfide exchange cascade. The final step in the cascade involves reduction of the Cys(103)-Cys(109) disulfide of nDsbD by Cys(461) of cDsbD. Here we show that a complex between the globular periplasmic domains is trapped in vivo only when both are linked by tmDsbD. We have found previously ( Mavridou, D. A., Stevens, J. M., Ferguson, S. J., and Redfield, C. (2007) J. Mol. Biol. 370, 643-658 ) that the attacking cysteine (Cys(461)) in isolated cDsbD has a high pK(a) value (10.5) that makes this thiol relatively unreactive toward the target disulfide in nDsbD. Here we show using NMR that active-site pK(a) values change significantly when cDsbD forms a complex with nDsbD. This modulation of pK(a) values is critical for the specificity and function of cDsbD. Uncomplexed cDsbD is a poor nucleophile, allowing it to avoid nonspecific reoxidation; however, in complex with nDsbD, the nucleophilicity of cDsbD increases permitting reductant transfer. The observation of significant changes in active-site pK(a) values upon complex formation has wider implications for understanding reactivity in thiol:disulfide oxidoreductases.